Kebangkitan Perspektif Islam dalam Studi Hubungan Internasional Kontemporer - Muhammad Qobidl ‘Ainul Arif (Dauliyah Journal of Islamic and International Affairs, 2016)
Since its inception in 1919 from “the womb” of Western civilization, International Relations could not escape from the domination of Western empirical experiences, logics, cultures and worldviews. Islamic perspective as an alternative thought as well as analytical lens in contemporary International Relations appeared on the surface at the end of twentieth century. However, the study of Islamic perspective in International Relations was actually started as early as the middle of the second century of Hijrah within the discipline of Siyar. Islamic perspective in International Relations contained unique principles and way of thinking differed from Western tradition. This article showed how actually Islamic perspective had been applied in the study of relations among nations since Prophet Muhammad Shallallahu ‘Alaihi Wasallam until contemporary Islamic scholars and Islamic law jurists’ era. In Indonesia, the wave of Islamic high learning institutions transformation status at the end of President Susilo Bambang Yudhoyono’s government also opened the gate for awakening of Islamic perspective application in the field of International Relations. This was no wonder as the study of Islamic perspective in International Relations already had its own history, tradition, and basic philosophy.